Cajal and his love for Nature: a sentimental essence in the legacy of neurosciences - Garrido, Eduardo (Frontiers in Neuroanatomy, 2024)
Santiago Ramón y Cajal (1852–1934) revolutionized the branches of neuroscience in a forceful way, and he did it with extreme delicacy and candor. His scientific writings and drawings are full of allusions to Nature, a fact that demonstrates how he saw, understood and enjoyed it with exquisite sensitivity and pressing emotion. Neuroscience awakened in him the utmost curiosity to delve into the powerful mysteries of the mind, and neurohistology allowed him to satisfy his deepest concerns for fascinating scenarios, a desire not sufficiently fulfilled throughout the fields, mountains and forests of his childhood and youth. Through that wonderful microscopic world Cajal changed the size of the dreamed landscapes but not the dimension of the longed-for adventures. Exploring and entering unknown paths he unraveled some of the greatest enigmas that the nervous system hid, but he would do so with a deep feeling toward the infinite beauty that Nature itself offered him. In short, Nature was the vital axis of Cajal’s overwhelming and complex personality, his most genuine essence and the inexhaustible source of inspiration where he poured his imagination and fantasy. He became a vocational adventurer, an insatiable explorer, a talented artist and an exquisite humanist. An eminently romantic soul who knew how to link Nature and Neuroscience with unconditional and perpetual emotionality.